Unraveling the Role of Supramolecular Additives in a Proline‐Catalyzed Reaction. Issue 1 (6th December 2018) - Martín, Judith; Merino, Isabel; Fanjul‐Mosteirín, Noé; Mendoza‐Meroño, Rafael; García‐Granda, Santiago; Concellón, Carmen; del Amo, Vicente
Abstract : Various additives, typically based on molecules featuring H‐bond donor motifs, have been essayed towards improving the catalytic properties of proline. However, their mode of action is not clear yet. By employing in situ 1 H and 19 F NMR DOSY experiments, the role of a tetrafluoroborate guanidinium salt in a novel proline‐catalyzed cross‐aldol reaction between α, α‐dichloroacetone and aromatic aldehydes has been fully disclosed. Abstract : The cooperative participation of a TBD‐derived guanidinium salt and proline promotes the cross‐aldol reaction between α, α‐dichloroacetone and aromatic aldehydes. NMR DOSY experiments allow disclosing the mode of action of this additive, which operated through H‐bonding interactions.